EFEKTIVITAS GAYA MENGAJAR INTERAKSIONAL TERHADAP MINAT BELAJAR SISWA KELAS VI SD MUHAMMADIYAH 1 TEGAL - Azam Syukur Rahmatullah; Moh. Toriqul Chaer (Institut Kariman Wirayudha Sumenep, 2022)
Education is a lifelong process and the embodiment of self-formation as a whole. The development of potential for fulfilling human commitments as individuals, as social beings, and as creatures of God. The purpose of this study is to find out how the teacher's teaching style is, how the students' interest in learning is, and to find out the influence between the teacher's teaching style and the student's attention to learning at SD Muhammadiyah 1 Tegal. This research is qualitative research. This research is true experimental research using a qualitative approach. The results showed that the teacher had a learning method to impart knowledge from a religious and social perspective, and train students to be independent and responsible. Face-to-face learning was temporarily suspended due to the Covid-19 pandemic, so the teacher's interactional teaching style used the Zoom and Whatsapp learning media. Learning interests vary from student to student, and the teacher's assignment is to provide learning stimulus in the form of motivation and encouraging students. The interactional teaching style is related to students' interest in learning because a good teaching style makes students easy to be interested in and understand the material presented by the teacher